2022
DOI: 10.1002/acm2.13545
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radiation dose to pediatric models from whole body PET/CT imaging

Abstract: Positron emission tomography (PET)/computed tomography (CT) is a well‐known modality for the diagnosis of various diseases in children and adult patients. On the other hand, younger patients are more radiosensitive than adults, so there are concerns about the level of ionizing radiation exposure in pediatric whole body PET/CT imaging. In this regard, comprehensive specific radiation dosimetry for whole body PET/CT imaging is highly desired for different ages, sizes, and shapes. Therefore, in this study, organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…93 Mohammadi et al suggested that any modeling used to assess dose from these scintigraphic studies should ensure a variety of ages, and anatomies are used for accurate dose evaluation. 94 PET/MRI systems can further reduce the radiation exposure by utilizing MRI instead of CT for attenuation correction for the PET imaging. The MRI imaging will determine the length of the PET acquisition because it is usually longer than optimal PET acquisition per area of body imaged.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…93 Mohammadi et al suggested that any modeling used to assess dose from these scintigraphic studies should ensure a variety of ages, and anatomies are used for accurate dose evaluation. 94 PET/MRI systems can further reduce the radiation exposure by utilizing MRI instead of CT for attenuation correction for the PET imaging. The MRI imaging will determine the length of the PET acquisition because it is usually longer than optimal PET acquisition per area of body imaged.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Mohammadi et al. suggested that any modeling used to assess dose from these scintigraphic studies should ensure a variety of ages, and anatomies are used for accurate dose evaluation 94 …”
Section: Nuclear Medicinementioning
confidence: 99%
“…The calculation of radiation dose for pediatric patients undergoing PET studies requires sophisticated consideration of two main factors: patient modeling and radiopharmaceutical biodistribution. Many kinds of anthropomorphic phantoms with different age, sex and size have been established to model patients and their dosimetry properties (Khamwan et al 2018, Mohammadi and Akhlaghi 2022, Ferreira et al 2023. However, reference phantoms may cause considerable uncertainty in dose estimation due to the variation in whole-body properties among individuals (Neira et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to adult CT, pediatric CT may significantly increase the estimated risk of death from cancer (18). The lifetime attributable risks of all cancer morbidity and mortality in 10-year-old children (males and females) were almost 5.29 and 3.16 times that of 70-year-old adults (men and women), and these risks were even greater for younger children (19). Thus, it is of clinical significance to reduce the radiation dose while ensuring the quality of PET/CT images in children.…”
Section: Introductionmentioning
confidence: 99%